2021
DOI: 10.3389/fsurg.2021.746784
|View full text |Cite
|
Sign up to set email alerts
|

Local Excision ± Chemoradiotherapy vs. Total Mesorectal Excision for Early Rectal Cancer: Case-Matched Analysis of Long-Term Results

Abstract: Background: Our aim was to compare the bowel function and oncologic outcomes following these two treatment modalities.Materials and methods: This was a single-center study with 67 patients included between 2009 and 2018. A total of 32 patients underwent total mesorectal excision (TME) group and 35 transanal local excisions (LE) ± chemoradiation. We performed a case-matched analysis: we matched the patients by age, cancer stage, and comorbidities. Duration of operation, postoperative complications, length of ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…In addition, this study found no statistically significant differences in recurrent metastases and overall survival with or without adjuvant therapy after TEM. These findings are similar to the results of a recent study, concluding that survival after transanal local excision with or without chemoradiotherapy is comparable to that of TME, while TEM allows better bowel function and postoperative quality of life ( 54 ).…”
Section: Discussionsupporting
confidence: 89%
“…In addition, this study found no statistically significant differences in recurrent metastases and overall survival with or without adjuvant therapy after TEM. These findings are similar to the results of a recent study, concluding that survival after transanal local excision with or without chemoradiotherapy is comparable to that of TME, while TEM allows better bowel function and postoperative quality of life ( 54 ).…”
Section: Discussionsupporting
confidence: 89%
“…Radical surgery carries a 2-3% risk of perioperative mortality and a 20-30% complication rate, including the need for permanent colostomy [41]. To mitigate these potential problems, local excision with adjuvant chemoradiotherapy have been demonstrated as an alternative to radical surgery in early stage rectal cancer patients [42,43]. Although NCCN guideline suggested transabdominal resection for T2 stage rectal cancer patients, local excision with chemoradiotherapy had been demonstrated to be a feasible alternative to radical surgery [13,44,45].…”
Section: Discussionmentioning
confidence: 99%
“…These include surgical options such as local excision techniques or radical surgery 1 , 2 . Patients with early rectal cancer without poor prognostic features may be offered local excision with or without adjuvant chemoradiotherapy 3 .…”
mentioning
confidence: 99%